Development of models and methodologies for optimizing electric power system reliability - Del Mundo, Rowaldo R. (1991)
The importance of optimizing the level of reliability of electric power system cannot be over-emphasized. Consumers of electricity suffer inconvenience and economic losses for every power interruption. The Electric utility, on the other hand, is constrained by several economic factors to meet the high reliability requirements of customers. And like any product in the market, the higher the reliability is, the more costly the power supply will be. To quantify the losses to consumers and to determine the optimal level of reliability of power system, analytical models and methodologies were developed in this study. Practical studies were conducted in order to apply and validate the models and techniques developed. A survey of power outages in the industrial sector of Metro Manila was conducted. Optimal level of reliability was determined for NPC Luzon Grid using a computer program developed by the author for the study.